Validation of Monte Carlo 131I radiopharmaceutical dosimetry workflow using a 3D‐printed anthropomorphic head and neck phantom. Issue 8 (6th June 2022) - Adam, David P.; Grudzinski, Joseph J.; Bormett, Ian; Cox, Benjamin L.; Marsh, Ian R.; Bradshaw, Tyler J.; Harari, Paul M.; Bednarz, Bryan P.
Abstract: Purpose: Approximately 50% of head and neck cancer (HNC) patients will experience loco‐regional disease recurrence following initial courses of therapy. Retreatment with external beam radiotherapy (EBRT) is technically challenging and may be associated with a significant risk of irreversible damage to normal tissues. Radiopharmaceutical therapy (RPT) is a potential method to treat recurrent HNC in conjunction with EBRT. Phantoms are used to calibrate and add quantification to nuclear medicine images, and anthropomorphic phantoms can account for both the geometrical and material composition of the head and neck. In this study, we present the creation of an anthropomorphic, head and neck, nuclear medicine phantom, and its characterization for the validation of a Monte Carlo, SPECT image‐based, 131 I RPT dosimetry workflow. Methods: 3D‐printing techniques were used to create the anthropomorphic phantom from a patient CT dataset. Three 131 I SPECT/CT imaging studies were performed using a homogeneous, Jaszczak, and an anthropomorphic phantom to quantify the SPECT images using a GE Optima NM/CT 640 with a high energy general purpose collimator. The impact of collimator detector response (CDR) modeling and volume‐based partial volume corrections (PVCs) upon the absorbed dose was calculated using an image‐based, Geant4 Monte Carlo RPT dosimetry workflow and compared against a ground truth scenario. Finally, uncertainties were quantified in accordance with recent EANM guidelines. Results: The 3D‐printed anthropomorphic phantom was an accurate re‐creation of patient anatomy including bone. The extrapolated Jaszczak recovery coefficients were greater than that of the 3D‐printed insert (∼22.8 ml) for both the CDR and non‐CDR cases (with CDR: 0.536 vs. 0.493, non‐CDR: 0.445 vs. 0.426, respectively). Utilizing Jaszczak phantom PVCs, the absorbed dose was underpredicted by 0.7% and 4.9% without and with CDR, respectively. Utilizing anthropomorphic phantom recovery coefficient overpredicted the absorbed dose by 3% both with and without CDR. All dosimetry scenarios that incorporated PVC were within the calculated uncertainty of the activity. The uncertainties in the cumulative activity ranged from 23.6% to 106.4% for Jaszczak spheres ranging in volume from 0.5 to 16 ml. Conclusion: The accuracy of Monte Carlo‐based dosimetry for 131 I RPT in HNC was validated with an anthropomorphic phantom. In this study, it was found that Jaszczak‐based PVCs were sufficient. Future applications of the phantom could involve 3D printing and characterizing patient‐specific volumes for more personalized RPT dosimetry estimates.